2021
DOI: 10.1016/j.jsps.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Calming the inflammatory storm in severe COVID-19 infections: Role of biologics- A narrative review

Abstract: The risk of Coronavirus infection continues, and the fear of resurgence indicates the lack of a successful therapeutic strategy. In severe COVID-19 infection, many immune cells and their products are involved, making management difficult. The abundant release of cytokines and chemokines in severe COVID-19 patients leads to profound hyper inflammation and the mobilization of immune cells, triggering the cytokine storm. The complications associated with the cytokine storm include severe respiratory distress, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In addition, COVID-19 can activate the PI3K-Akt signaling pathway and can play dual anti-inflammatory and carcinogenic roles [ 48 ]. The JAK-STAT signaling pathway that activates cytokines has been suggested as a target for preventing intense lung injury and increasing the chances of survival in COVID-19 patients [ 49 ]. More importantly, a genetic polymorphism study of COVID-19 patients showed the polymorphism locus near the Janus kinase (JAK) TYK2, the key for IFN, interleukin (IL)-12, and IL-23 signaling, and T helper (Th) 1/Th17 cell mediated antiviral immune responses, suggesting the critical role of the JAK-STAT signaling pathway in the development of cytokine storm in COVID-19 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, COVID-19 can activate the PI3K-Akt signaling pathway and can play dual anti-inflammatory and carcinogenic roles [ 48 ]. The JAK-STAT signaling pathway that activates cytokines has been suggested as a target for preventing intense lung injury and increasing the chances of survival in COVID-19 patients [ 49 ]. More importantly, a genetic polymorphism study of COVID-19 patients showed the polymorphism locus near the Janus kinase (JAK) TYK2, the key for IFN, interleukin (IL)-12, and IL-23 signaling, and T helper (Th) 1/Th17 cell mediated antiviral immune responses, suggesting the critical role of the JAK-STAT signaling pathway in the development of cytokine storm in COVID-19 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…GM‐CSF activates the JAK2/STAT3/STAT5 signaling pathway by binding to the β‐chain subunit of the GM‐CSF receptor, thereby regulating the massive release of cytokines, such as IL‐1, IL‐6, and TNF‐α from immune cells (such as DCs, monocytes, and macrophages). 129 , 130 In addition, GM‐CSF‐R may activate other downstream signals, including the activation of NF‐κB and PI3K‐Akt. 131 Thus, regulation of GM‐CSF and its signaling is an important way to improve inflammation in COVID‐19.…”
Section: Inflammatory Pathways In Covid‐19mentioning
confidence: 99%
“…JAK/STAT is initially activated by binding of cytokines, such as IFNα/β, IFNγ, and IL-6. IFNα/β employs TYK2 and JAK1 to phosphorylate STAT1 and STAT2, IFNγ recruits JAK1 and JAK2 to phosphorylate STAT1, and IL-6 leads to one or both JAK-mediated phosphorylations of STAT3 ( Majoros et al, 2017 ; Banji et al, 2021 ). These activated STAT dimers are then transported to the nucleus and promote the transcription of interferon stimulated genes (ISGs; Raftery and Stevenson, 2017 ).…”
Section: Trim Regulation Of Innate Immune Responsementioning
confidence: 99%